Temperature-dependent spectroscopic evidences of curcumin in aqueous medium: a mechanistic study of its solubility and stability - Jagannathan, Ramya; Abraham, Priya Mary; Poddar, Pankaj (Journal of Physical Chemistry B, 2012)
In curcumin, keto-enol-enolate equilibrium of the heptadiene-dione moiety determines its physiochemical and antioxidant properties. However, its poor solubility in water at neutral pH and room temperature decreases its bioavailability. Potential therapeutic applications have triggered an interest in manipulating the solubility of curcumin in water as its stability and solubility in water remains poorly understood. Here, the mechanism behind its solubility at various temperatures and the influence of interplay of temperature, intramolecular H-bonding, and intermolecular forces is reported, which leads to aggregation-disaggregation at various temperatures. Remarkable change is observed in temperature-dependent electronic transition behavior of curcumin, however, the absorption spectra after cooling and heating cycles remain unchanged, hinting much better thermal stability of curcumin in water than previously thought. This study indicates that it is perhaps the breaking of intramolecular hydrogen bonding which leads to exposure of polar groups and hence responsible for the dissolution of curcumin at higher temperature. The formation of intermolecular aggregates might be responsible behind a better room temperature stability of the molecules after cooling its aqueous suspension from 90 to 25 degrees C. These curcumin solubility studies have great application in biological research with reference to bioavailability and to understand target oriented mode of action of curcumin.